Epidemiological Outbreak Investigation of Chickenpox in Baidauli VDC, Nawalparasi, Nepal - Poudel, Ram Chandra; Munikar, Sabika; Acharya, Biswanath; Shrestha, Gambhir; Thapa, Kanchan (Journal of College of Medical Sciences-Nepal, 2019)
Background: On 2015, a cluster of chickenpox like symptoms was reported in Baidauli VDC of Nawalparasi, Nepal. This study aims to report the outbreak investigation and guide preventive and control measures. Methods: This investigation was conducted in Baidauli VDC of Nawalparasi, Nepal where a large number of cases with infectious rashes with fever was reported. Data were collected using a semi-structured questionnaire comprising of socio-demographic characteristics and clinical features. A detailed clinical examination of the cases was also performed. The outbreak was described by time, place and person and the epidemiological curve drawn. Results: A total of 55 cases from 27 households were affected by chickenpox. The outbreak continued for 45 days. The number of cases peaked (n=25) one month after detection of the primary case. The last case was reported after 15 days of the peak. The commonest age group affected was 5 to 15 years with a mean of 11.3 years (SD 8.9). The mean duration of rashes was 7.2 days (SD 1.7) which ranged from 3 days to 12 days. All the cases had rashes on head/face, trunk, arm and legs, and some had rashes inside the mouth (n=8) and palm (n=5). Almost 95% (n=52) cases experienced fever. Conclusions: This study concluded that there was an outbreak of chickenpox. The signs and symptoms of the disease were due to chicken pox infection. Immediate preventive and control measures were recommended to halt the spread of the disease. Health education and awarness regarding the preventive measures of disease should be promoted.